حدود سلطة الادارة في الاستيلاء المؤقت علي الاموال الخاصة مشرف كمال فتحي ادريس الطالبين رياض بن علي وياسين تواتي - بن علي, رياض; تواتي, ياسين (University of Eloued جامعة الوادي, 2020)
إن تحقيق المصمحة العامة هو الهدف الأسمى الذي ترمي الإدارة إلى تحقيقه، وتقوم في سبيل ذلك باستعمال امتيا ا زت المصمحة العامة مصدرتا ق ا ر ا رت إدارية وتصرفات مادية لموصول إلى أهدافها المنشودة. لكن قد تط أ ر ظروف استعجالية أو استثنائية يستحيل معها تحقيق المصمحة العامة باستخدام الأدوات والوسائل القانونية المعتادة فتمجأ لمحصول عمى ما يمزمها إلى الاستيلاء المؤقت عمى الأموال الخاصة لضمان سير الم ا رفق العامة، مستخدمة السمطة التقديرية الممنوحة لها قانونا. لكن استعمال هذا الامتياز الممنوح لها بموجب القانون لا يتيح لها التعسف إلى درجة الإض ا رر بمصالح الخواص من خلال حرمانهم من ممكيتهم الخاصة، فالمشرع فرض ضوابط قانونية يجب إتباعها، كما أن لمقضاء دور أساسي يكمن في م ا رقبة مدى مشروعية ق ا ر ا رت الاستيلاء الصاد رة عن الإدارة، وتمكين المتضررين من تعويض عادل إذا لزم الأمر.The Achievement of the public good is the ultimate goal which the administration aims to achieve. And for that, it uses public interest privileges issuing administrative decisions and material actions to reach its desired goals. But urgent or exceptional circumstances may arise in which it is impossible to achieve the public good using the usual legal tools and means .It resorts to the temporary seizure of private funds to obtain what it needs to ensure the functioning of public facilities Using the discretion granted to it by law. But the use of this concession granted to it does not allow her to be arbitrary to the point of harming the interests of private individuals by depriving them of their private property. The legislator imposed legal controls that must be followed, as that Judiciary has an essential role lies in monitoring the legitimacy of the seizure decisions issued by the management and enable those affected to receive just compensation if necessary.
مذكرة ماستر
Keywords: الاستيلاء المؤقت – الأموال الخاصة – الظروف الاستثنائية – الرقابة القضائية.; Temporary seizure - Private money - Exceptional circumstances - Judicial oversight.